Optimal Supplier Selection and Order Allocation for Multi-Period Multi-Product Manufacturing Incorporating Customer Flexibility - Mak, K L; Cui, L X; Su, W (Engineering Letters, 2011)
Effective and efficient supplier selection and order allocation are essential for a manufacturer to ensure stable material flows in a highly flexible and competitive supply chain. This paper attempts to solve the problem of optimal supplier selection and order allocation for multi-period multi-product manufacturing when customer flexibility exists. A new mathematical model in the form of a mixed integer programming (MIP) model is developed to describe the characteristics of the problem. The objective is to maximize the manufacturer's profit subject to the various operating constraints of the supply chain. In addition, a new hybrid algorithm based on the strengths of constraint programming (CP) and simulated annealing (SA) is developed to solve this complex combinatorial optimization problem which is NP-hard. The developed algorithm is applied to solve a set of randomly generated test problems to evaluate its performance. Comparison of the computational results obtained with those obtained by using the commercial software ILOG OPL clearly shows that the methodology developed in this paper is an effective and efficient approach to assist the manufacturer in formulating optimal supplier selection and order allocation decisions.